Family caregivers' sense-making of the results of functional neurodiagnostics for patients with Prolonged Disorders of Consciousness. - Cruse D; Ragazinskaite K; Chinner A; Bareham C; Roberts N; Banner R; Chennu S; Villa D (Taylor and Francis Group, 2024)
Functional neuroimaging and electrophysiological assessments can identify evidence of residual consciousness and cognition in patients with prolonged disorders of consciousness (PDOC) who are otherwise behaviourally unresponsive. These functional neurodiagnostics are increasingly available in clinical settings and are recommended by international clinical guidelines to reduce diagnostic and prognostic uncertainty, and thereby assist family caregivers in their best-interests decision-making. Nevertheless, little is known about how family caregivers make sense of the results of these state-of-the-art functional neurodiagnostics. By applying Interpretative Phenomenological Analysis (IPA) to interviews with family caregivers of patients with diagnoses of PDOC who had received a functional neurodiagnostic assessment, we identify three primary themes of sense-making: The special significance of "brain scans"; A dynamic sense-making process; Holding on to hope and holding on to the person. These themes highlight the challenges of helping family caregivers to balance the relative importance of functional neurodiagnostic results with other clinical assessments and identify an ability of family caregivers to hold a contradiction in which they hope for recovery but simultaneously express a rational understanding of evidence to the contrary. We offer several recommendations for the ways in which family caregivers can be better supported to make sense of the results of functional neurodiagnostics.
Keywords: Disclosure; Disorders of consciousness; Interpretative phenomenological analysis; Neurodiagnostics; Sense-making